If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2+8x=-6
We move all terms to the left:
2+8x-(-6)=0
We add all the numbers together, and all the variables
8x+8=0
We move all terms containing x to the left, all other terms to the right
8x=-8
x=-8/8
x=-1
| -56=−7s−63 | | 3+2(4x-5)=5-3(2x+1) | | 40x+28=68 | | 18+15y=13y | | 3n+38=11+14 | | -2(j-10)=-14 | | 5x-19=4x+16 | | 3(x+9)=8x+5-5x+22 | | 5x-19=4x | | -2(6+5x)=-32 | | 146=-9w-7 | | 4x-10=-6x+20 | | 4x-10=-46-4x | | -126-4x=66-12x | | x+9+3x=4x+9 | | 6(-2-6x)=-48 | | 29x+1=59 | | 18x^2=-36x | | 0.6(x+200)=0.64x-192 | | -7(3+5x)=119 | | 12.2=-10.2+7w | | m+-12=3 | | x/64=9 | | 2x+72+x=180 | | -4(3-3x)=-48 | | 45=x+26 | | 0.3(3z+7)+17.7=0.7(3z-6) | | -6(5x+6)=-96 | | -2x+8+4x=40 | | 3(-10-3x)=-129 | | -9y-7=24y-4 | | -5x-9=−3x−9 |